Non-invasive cardiovascular imaging for evaluating subclinical target organ damage in hypertensive patients: A consensus paper from the European Association of Cardiovascular Imaging (EACVI), the European Society of Cardiology Council on Hypertension, and - Perrone-Filardi, Pasquale; Coca, Antonio; Galderisi, Maurizio; Paolillo, Stefania; Alpendurada, Francisco; De Simone, Giovanni; Donal, Erwan; Kahan, Thomas; Mancia, Giuseppe; Redon, Josep; Schmieder, Roland; Williams, Bryan; et al. (European Heart Journal - Cardiovascular Imaging, 2017)
Arterial hypertension (HTN) accounts for the largest amount of attributable cardiovascular (CV) mortality worldwide, and risk stratification in hypertensive patients is of crucial importance to manage treatment and prevent adverse events. Asymptomatic involvement of different organs in patients affected by HTN represents an independent determinant of CV risk and the identification of target organ damage (TOD) is recommended to further reclassify patients' risk. Non-invasive CV imaging is progressively being used and continues to provide new technological opportunities to TOD evaluation at early stage. The aim of this article is to provide the community of cardiology with an update on appropriate and justified use of non-invasive imaging tests in the growing population of hypertensive patients.
EVALuna2:4039